Engineering a Synthetic Pathway for Gentisate in Pseudomonas Chlororaphis P3 - Wang, Songwei; Fu, Cong; Liu, Kaiquan; Cui, Jiajia; Hu, Hongbo; Wang, Wei; Zhang, Xuehong (Frontiers in Bioengineering and Biotechnology, 2021)
Pseudomonas chlororaphis P3 has been well engineered as a platform organism for biologicals production due to enhanced shikimate pathway and excellent physiological and genetic characteristics. Gentisate displays high antiradical and antioxidant activities and is an important intermediate that can be used as a precursor for drugs. Herein, a plasmid-free biosynthetic pathway of gentisate was constructed by connecting the endogenous degradation pathway from 3-hydroxybenzoate in Pseudomonas for the first time. As a result, the production of gentisate reached 365 mg/L from 3-HBA via blocking gentisate conversion and enhancing the gentisate precursors supply through the overexpression of the rate-limiting step. With a close-up at the future perspectives, a series of bioactive compounds could be achieved by constructing synthetic pathways in conventional Pseudomonas to establish a cell factory.